Falhas de governança: levantamento de casos no mercado de capitais - Meirinho, Marcia Regina Sá de Sousa (2016)
This study aimed to identify the governance failures that allow the occurrence of fraud, embezzlement as well as financial and reputational losses in listed companies. Therefore, a study of multiple cases was conducted involving five public companies, from which four are traded on the São Paulo Stock Exchange (BOVESPA). Data was obtained from interviews with experienced stock market professionals and other secondary sources that were confronted in the light of the Theory of Agency, which examined the relationship between owner and agent or managers. Two critical points were addressed in the interviews: primarily the work of the Board of Directors, which requires higher skills and willingness to deal with strategic issues relevant to the company. The second point was the motivation of agents who at times apply opportunistic practices to benefit themselves at the expense of the company's interests, which in turn creates the need for instruments and mechanisms for monitoring and control of the manager's performance. Corporate governance is not only related to the implementation of good practices and rules, but rather to the most efficient way to enhance decision making in business, so that managers, shareholders and Board of Directors have a voice and unify efforts to bring better results for the company.